Implementasi Pengajaran Rasul Paulus Tentang Nasehat Hidup Bersatu Dan Merendahkan Diri Seperti Kristus Berdasarkan Filipi 2:1-30 Dikalangan Gembala Sidang GPdI Se- Jawa Tengah - Esra Sitanggang; Muner Daliman; Hana Suparti; Sri Wahyuni (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2020)
The purpose of this study is to determine the level of implementation of the teaching of the Apostle Paul about the Advice to Live Together and Humble Yourself Like Christ Based on Philippians 2: 1-30 Among Pastors of the GPdI Council in Central Java. At the same time, the dominant dimensions and backgrounds determine the implementation of the Apostle Paul's Teaching among the Pastors of the GPdI Council in Central Java. The methodology used in this study is a quantitative method using a questionnaire and literature review. The literature contains the exegesis of Bible verses from Philippians 2: 1 - 30 which are contained in the dimension of advice to live together which is described in 9 supporting indicators and the dimension of advice to humble oneself like Christ which is explained in 8 supporting indicators. The results of this study indicate that: 1. The level of implementation of the Apostle Paul's Teaching on the Advice to Live One and Humble Yourself Like Christ Based on Philippians 2: 1-30 Among the Pastors of the GPdI Council in Central Java is in the high category; 2. The dominant dimension is to humble oneself like Christ (D2) and the dominant background is the number of congregations.